Attack of the tyrannosaurus - Stone, Rex. (Little apple, 2008)
"Tom and Jamie can't believe their luck when they find a secret entrance to a prehistoric world filled with dinosaurs! The first dinosaur they meet is a friendly wannanosaurus. It eats the fruit from super-stinky ginkgo trees. But soon, Tom and Jamie meet a much less friendly dino--a Tyrannosaurus rex that would like to eat them!"--P. [4] of cover.